FAKTOR - FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN SERTA DAMPAKNYA TERHADAP AKUNTABILITAS ORGANISASI (Studi pada Universitas Brawijaya Malang) - Ipma Rahman Yudanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The aim of this study is to predict the influence of leadership style, compensation system suitability, internal control effectiveness and accounting procedures adherence on fraud tendency and its impact on organizational accountability in government agencies. This studyuses a convenience sampling method in primary data collection with a sample of 160 respondents. Data analysis method used is multiple regression analysis. Results show that leadership style, compensation system suitability, internal control effectiveness and accounting procedures adherence negatively affect fraud tendency as well as fraud propensity has a negative effect on organizational accountability. The results of this study indicate that the leadership style have a dominant influence in affecting the tendency of fraud. It shows that the type of a leader to lead can affect the performance of employees and it can be used by UB to suppress fraud tendencies. Other things which can be used to reduce fraud tendency are recognizing and appreciating employees, setting realistic goals for the institution, delivering a clear direction and desired objectives, inspiring subordinates and giving praise or rewards to employees who complete tasks on time.Keywords: Fraud tendency, leadership style, compensation system suitability, internal control effectiveness, accounting procedures adherence, accountability, Brawijaya University.